2004
DOI: 10.1196/annals.1306.010
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Basis of Manganese Neurotoxicity

Abstract: Exposure to excessive levels of manganese, an essential trace element, can evoke severe psychiatric and extrapyramidal motor dysfunction closely resembling Parkinson's disease. The clinical manifestations of manganese toxicity arise from focal injury to the basal ganglia. This region, characterized by intense consumption of oxygen and significant dopamine content, can incur mitochondrial dysfunction, depletion of levels of peroxidase and catalase, and catecholamine biochemical imbalances following manganese ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
101
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 119 publications
(105 citation statements)
references
References 42 publications
3
101
0
1
Order By: Relevance
“…While DES exhibited substantial protective effects for MnCl 2 even at a concentration of 1μM, only 10μM DES had protective effects against 10μM MnPO 4 with little to no protective ability when incubated with 100μM MnPO 4 . Previous studies indicate that the pro-oxidant activity of MnCl 2 is exhausted in the presence of 500-fold lower concentrations of desferioxamine (HaMai and Bondy, 2004). Data from the present study appears to support the presence of trace amounts of Mn 3+ in MnCl 2 solutions and corrobate this finding.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…While DES exhibited substantial protective effects for MnCl 2 even at a concentration of 1μM, only 10μM DES had protective effects against 10μM MnPO 4 with little to no protective ability when incubated with 100μM MnPO 4 . Previous studies indicate that the pro-oxidant activity of MnCl 2 is exhausted in the presence of 500-fold lower concentrations of desferioxamine (HaMai and Bondy, 2004). Data from the present study appears to support the presence of trace amounts of Mn 3+ in MnCl 2 solutions and corrobate this finding.…”
Section: Discussionsupporting
confidence: 86%
“…One hypothesis put forth to explain Mn neurotoxicity is that Mn 2+ can undergo redox cycling reactions with Mn 3+ leading to dopaminergic toxicity, with Mn 3+ being the reactive species responsible for toxicity (Archibald and Tyree, 1987). The increased toxicity of Mn 3+ can be partially explained by the four unpaired d orbital electrons which results in a highly unstable atom with an elevated redox potential compared to the more thermodynamically stable Mn 2+ (HaMai and Bondy, 2004). Archibald and Tyree (1987) demonstrated that when L-DOPA was added to a physiological buffer containing Mn 3+ -pyrophosphate, a discernable color change was produced.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations